Feasibility Power Control on Cognitive Radio Network with Fixed Power of Primary User - Amalia, Norma; Hikmaturokhman, Alfin (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2024)
Frequency spectrum is a limited resource that is strictly determined by static spectrum policy. As every part of the spectrum is already allocated to several certain services, only a portion can be obtained. On the other hand, as the user’s demand for reliable communication systems is increasing rapidly, a new paradigm of communication systems is needed. It is compulsory for existing spectrum can handle the increasing number of users, as cognitive radio technology could well address this issue. One crucial key of this technology is its power control. In this paper, the power control based on a feasible solution is studied. The PU has fixed power, the SU power is controlled using the power control method. The non-negative power vector is limited by the initial power . The output parameters of this simulation are the FSPC effect to the performance of SU and PU, the SU’s  impact on the feasible solution, and the feasible solution probability. In the  constraint, the PU SIR  rises from 14 dB to 22 dB upon implementing a FSPC. The PU SIR is contrary to the SIR of SU. When the target of the SU’s SIR is increased, the SIR value of the PU is decreased. As well as when the  value of the SU increases, the greater the SIR of the SU, the lower the SIR of the PU. If the power control is feasible, both PU and SU can simultaneously meet the target SIR. Considering the primary user's (PU) power remains fixed, the PU, as the main user, can determine its own power without being influenced by the SU power.